2020
DOI: 10.1074/jbc.ra120.013012
|View full text |Cite
|
Sign up to set email alerts
|

Modulating functional amyloid formation via alternative splicing of the premelanosomal protein PMEL17

Abstract: The premelanosomal protein (PMEL17) forms functional amyloid fibrils involved in melanin biosynthesis. Multiple PMEL17 isoforms are produced, two of which arise from excision of a cryptic intron within the amyloid-forming repeat (RPT) domain, leading to long (lRPT) and short (sRPT) isoforms with 10 and 7 imperfect repeats, respectively. Both lRPT and sRPT isoforms undergo similar pH-dependent mechanisms of amyloid formation and fibril dissolution. Here, using human PMEL17, we tested the hypothesis that the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…This suggests that prion cross-infectivity is generally adjusted through a templateassisted mechanism that depends on strain-relevant structural conformation compatibility [169,227]. Unilateral cross-aggregation templating by alternative spliceoforms or naturally occurring glycosaminoglycans is an additional conformation-specific strategy used for the formation of functional amyloid in higher organisms [228,229].…”
Section: Hetero-aggregation In Functional Amyloidsmentioning
confidence: 99%
“…This suggests that prion cross-infectivity is generally adjusted through a templateassisted mechanism that depends on strain-relevant structural conformation compatibility [169,227]. Unilateral cross-aggregation templating by alternative spliceoforms or naturally occurring glycosaminoglycans is an additional conformation-specific strategy used for the formation of functional amyloid in higher organisms [228,229].…”
Section: Hetero-aggregation In Functional Amyloidsmentioning
confidence: 99%
“…Given the epidemiological context of melanoma among PD patients, we chose cross-seeding experiments where preformed α-syn fibrils, which accumulate in PD, were added to soluble Pmel17 RPT (residues 315 to 444), an essential domain for fibril formation in melanosomes (11). α-Syn and RPT fibril seeds were generated by continuous agitation in pH 6 buffer, mimicking the acidic conditions of the melanosome as previously described (12). Visualization by transmission electron microscopy (TEM) showed a mixture of rod-like (arrows) and twisted (brackets) fibril morphologies for α-syn ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Arrow indicates a distinctive feature (1,250 cm −1 ) in self-seeded RPT fibrils, that is less prominent in cross-seeded and α-syn fibrils. Self-seeded RPT data are reproduced from previous work ( 12 ). ( G ) Schematic representation of cathepsin L limited digestion, where lines represent cleavage sites ( Top ) and peptide fragments ( Bottom ) observed in both self-seeded and cross-seeded RPT fibrils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-seeding between family members as a possible means to regulate functional amyloid assembly has not yet been established in mammals. However, recent studies showed that alternative splicing within the amyloidogenic repeat domain of human PMEL, which forms an amyloid integral for melanin synthesis, resulted in an isoform that served as a nucleator to facilitate the amyloidogenesis of the longer PMEL form ( 19 ). These studies revealed a different mechanism to achieve the same result of a controlled nucleated polymerization as in E. coli .…”
mentioning
confidence: 99%